2023
DOI: 10.1002/anbr.202200144
|View full text |Cite
|
Sign up to set email alerts
|

Biominerallized Noble Metal‐Based RuO2 Nanozymes Against Myocardial Ischemic/Reperfusion Injury

Abstract: Myocardial ischemia/reperfusion (IR) injury is the leading cause of morbidity and mortality among elderly worldwide. Oxidative burst, which involves the rapid release of reactive oxygen species (ROS), is the primary mechanism of IR‐mediated myocardial dysfunction and injury. Therefore, ROS elimination shows great potential for modulating IR injury. Herein, BSA‐coated RuO2 nanoparticles (RuO2@BSA, RA NPs) as free radical scavengers are synthesized and their therapeutic effect against myocardial IR injury is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, these systems are severely disrupted during I/R, which contributes to excessive ROS production and leads to the initial myocardial reperfusion injury 33 . Thus, enhancing the activity of antioxidative enzymes may be a good strategy to decrease the oxidative stress‐elicited reperfusion damage 34,35 . Our previous work showed that F 2 protected against H/R model‐evoked oxidative injury in CMECs and myocytes 21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these systems are severely disrupted during I/R, which contributes to excessive ROS production and leads to the initial myocardial reperfusion injury 33 . Thus, enhancing the activity of antioxidative enzymes may be a good strategy to decrease the oxidative stress‐elicited reperfusion damage 34,35 . Our previous work showed that F 2 protected against H/R model‐evoked oxidative injury in CMECs and myocytes 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…33 Thus, enhancing the activity of antioxidative enzymes may be a good strategy to decrease the oxidative stress-elicited reperfusion damage. 34,35 Our previous work showed that F 2 protected against H/R model-evoked oxidative injury in CMECs and myocytes. 21,22 In agreement with these results, we found that the in vivo I/R-induced oxidative injury was also significantly alleviated by F 2 pretreatment.…”
Section: Ampk Interacts With Foxo1mentioning
confidence: 99%
“…ROS‐scavenging nanozymes with the specific action of mimicking SOD and CAT and protecting against ROS damage are promising targets in treating cardiac ischemic injury. [ 112 ] Nanozymes possess unique physicochemical properties and bioactivities that provide innovative opportunities to overcome the challenges in myocardial ischemia. For example, numerous metal‐based nanoparticles have inherent enzyme‐mimetic activities, such as CAT and SOD, which detoxify harmful O 2 • − and H 2 O 2 .…”
Section: Cat For Treating Myocardial Ischemic Diseasementioning
confidence: 99%
“…Intracellular antioxidants, such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), are crucial for maintaining balanced levels of ROS and reducing myocardial ischemic injury. These antioxidant enzymes work synergistically to convert toxic radicals into harmless products. , However, the therapeutic potential of natural enzymes is limited due to their high cost, low stability, and challenging storage. , Consequently, artificial nanomaterials with multienzyme activities have been developed to overcome these limitations for biomedical applications. MXenes, represented by the chemical formula M n +1 X n T x , are composed of ternary metal carbides/nitrides, where M denotes a transition metal (Ti, Mo, Ta, or Nb), X refers to carbon, nitrogen, or boron, and T represents surface groups (−O, −OH, −Cl, or −F). MXene-based biomaterials have garnered significant attention due to their intrinsic photothermal abilities, multiple enzyme-mimicking properties, and electrical conductivity. For instance, MXene, which has the ability to eliminate ROS, is a potential therapeutic candidate for treating ROS-related diseases such as hypertension, acute kidney injury, and ischemic stroke. Moreover, its high specific surface area and numerous anchoring sites enable specific metal ion absorption. For instance, Du and colleagues reported on the copper chelating ability of Nb 2 C for treating Alzheimer’s disease .…”
Section: Introductionmentioning
confidence: 99%